Modelling Electricity Futures Prices : Literature Review - Mikkonen, Rasmus (My University, 2026)
Electricity futures markets have important role in modern power systems by enabling market participants to manage price risk as the market is known by high volatility, non-storability, and increasing power generation uncertainty. This thesis reviews the theoretical and empirical literature on electricity futures pricing, focusing on the Nordic electricity market. The objective of the study is to show how electricity futures prices are formed and how expectations and risk premia are reflected in futures prices. The thesis is a literature review and the theoretical background consist classical commodity pricing theories, equilibrium-based risk premium models, and market efficiency perspectives. The theory explains the limitations of cost-of-carry pricing in electricity markets and to the expectations–risk premium framework commonly applied in the literature. The reviewed literature indicates that electricity futures prices are primarily driven by expectations of future spot prices combined with time-varying risk premia arising from weather-related uncertainty and structural characteristics of the electricity system. Empirical evidence from the Nordic market suggests that risk premia vary across seasons and maturities and are influenced by factors such as hydrological/weather conditions, renewable energy production forecasts, and transmission network capabilities. The findings highlight that electricity futures prices cannot be explained by traditional storage-based pricing models and that futures markets have crucial role in price discovery and risk management in the Nordic electricity market.

Sähköfutuurimarkkinoilla on tärkeä rooli nykyaikaisissa sähköjärjestelmissä, sillä ne mahdollistavat markkinaosapuolille hintariskin hallinnan, sillä markkinoille on ominaista korkea volatiliteetti, varastoimattomuus ja kasvava sähköntuotannon epävarmuus. Tässä opinnäytetyössä tarkastellaan sähköfutuurien hinnoittelua koskevaa teoreettista ja empiiristä kirjallisuutta keskittyen pohjoismaisiin sähkömarkkinoihin. Tutkimuksen tavoitteena on osoittaa, miten sähköfutuurien hinnat muodostuvat ja miten odotukset ja riskipreemiot heijastuvat futuurihinnoissa. Opinnäytetyö on kirjallisuuskatsaus, ja teoreettinen tausta koostuu klassisista hyödykkeiden hinnoitteluteorioista, tasapainoon perustuvista riskipreemiomalleista ja markkinoiden tehokkuusnäkökulmista. Teoria selittää sähkömarkkinoiden siirtokustannushinnoittelun rajoitukset ja kirjallisuudessa yleisesti käytetyn odotus-riskipreemio-kehyksen. Katsauksen perusteella sähköfutuurien hinnat määräytyvät ensisijaisesti tulevien spot-hintojen odotusten sekä vaihtelevien riskipreemioiden perusteella, jotka johtuvat säähän liittyvästä epävarmuudesta ja sähköjärjestelmän rakenteellisista ominaisuuksista. Pohjoismaisten markkinoiden empiirinen näyttö viittaa siihen, että riskipreemiot vaihtelevat vuodenaikojen ja maturiteettien mukaan ja niihin vaikuttavat tekijät, kuten hydrologiset/sääolosuhteet, uusiutuvan energian tuotantoennusteet ja siirtoverkon kapasiteetti. Tulokset korostavat, että sähköfutuurien hintoja ei voida selittää perinteisillä varastointiin perustuvilla hinnoittelumalleilla ja että futuurimarkkinoilla on ratkaiseva rooli hinnanmuodostuksessa ja riskienhallinnassa pohjoismaisilla sähkömarkkinoilla.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|